2019
DOI: 10.1007/s10841-019-00208-z
|View full text |Cite
|
Sign up to set email alerts
|

Hoverfly diversity (Diptera: Syrphidae) of Pyrenean oak woodlands in Central-Western Spain: a preliminary study with conservation outcomes

Abstract: Hoverflies are frequently used as biodiversity indicators and are targets of ecological studies across Europe. How hoverfly diversity responds to ecological variables is essential for species and habitat conservation. The present study is a first attempt to assess the hoverfly diversity of deciduous woodlands of Pyrenean oak (Quercus pyrenaica) in La Vera (Central-Western Spain), a habitat in need of conservation and a region that is poorly known in terms of hoverflies. Hoverflies were sampled with hand net in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…As in the case of the evolutionary diversity, there are several measures or indices (Petchey & Gaston, 2006;Mouchet, Villéger, Mason, & Mouillot, 2010), but the key question is always which species traits to study. In Syrphidae several morphological and biological species traits have been surveyed in the literature (e.g., larval microhabitat, larval feeding mode, adult body size, wing length, adult diet, development duration, inundation tolerance, migratory status, number of generations, among others), but the larval feeding mode has been mostly used to divide the species into "functional groups" (de Groot & Vrezec, 2019;Debeljak, Tosser, Sarthou, Kuzmanovski, & Trajanov, 2019;Djellab, Mebarkia, Neffar, & Chenchouni, 2019;Gaytán, Ricarte, & González-Bornay, 2020;Larrieu, Cabanettes, & Sarthou, 2015;Naderloo & Rad, 2014;Schweiger et al, 2007).…”
Section: Conservation Of the Loveridgeana Cladementioning
confidence: 99%
“…As in the case of the evolutionary diversity, there are several measures or indices (Petchey & Gaston, 2006;Mouchet, Villéger, Mason, & Mouillot, 2010), but the key question is always which species traits to study. In Syrphidae several morphological and biological species traits have been surveyed in the literature (e.g., larval microhabitat, larval feeding mode, adult body size, wing length, adult diet, development duration, inundation tolerance, migratory status, number of generations, among others), but the larval feeding mode has been mostly used to divide the species into "functional groups" (de Groot & Vrezec, 2019;Debeljak, Tosser, Sarthou, Kuzmanovski, & Trajanov, 2019;Djellab, Mebarkia, Neffar, & Chenchouni, 2019;Gaytán, Ricarte, & González-Bornay, 2020;Larrieu, Cabanettes, & Sarthou, 2015;Naderloo & Rad, 2014;Schweiger et al, 2007).…”
Section: Conservation Of the Loveridgeana Cladementioning
confidence: 99%
“…In total, 13 species and 210 individuals of hoverflies were recorded from forest habitats, while 11 species and 163 individuals were recorded from grassland (Figure 4). Gaytán et al (2020) also observed the greater abundance and species richness of hoverflies in a forest than in grassland habitats. The outcome of our study can be compared with the results of a research carried out by Ricarte et al (2011), who suggested that the highest number of species in the forest were observed possibly because of the availability of large varieties of resources, as well as the formation of different microhabitats such as over matured trees, small grasses, bodies of water (temporary or permanent), small invasive areas of scrub, forest edges, etc.…”
Section: Hoverfly Community In Two Habitatsmentioning
confidence: 66%
“…Hoverflies are generally mobile species, so they could be good bioindicators on landscape scales, whereas few philopatric species could be utilized as biodiversity indicators on microhabitat levels (Talasova et al 2018). Besides the complex relationships between pollinators and plants, recognizing the role of hoverflies in the ecosystem requires understanding their taxonomy, abundance, diversity, and responses to climatic factors (Gaytán et al 2020;Ela et al 2021). The information about hoverfly communities concerning biotic and abiotic factors has been generally documented with the concept of establishing many conservation strategies (Shebl et al 2008) that can help to avoid the loss of many wild plant species, prevent the decline in crop production and 5383 maintain the ecological balance (Rotheray and Gilbert 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These edge microclimatic conditions may alter insect communities and the processes in which they are involved. Although there is substantial evidence about edge effects on insect diversity and abundance, and on interspecific relationships such as pollination, herbivory, predation, and parasitism (Ries et al, 2004;Chacoff & Aizen, 2006;Valladares et al, 2006;Wirth et al, 2008;Gaytán et al, 2020), little is known about the effect of differently oriented edges mediated by changes in microclimatic conditions (Kautz et al, 2013;Bernaschini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%